THE DEVELOPMENT OF TSTS TEACHING STRATEGY WITH OUTDOOR LEARNING METHOD IN SYSTEM OF LINEAR EQUATION AND INEQUALITY MATERIAL - Nurul Kustiyati; Mardiyana Mardiyana; Ikrar Pramudya (Proceedings Education and Language International Conference, 2017)
This study began with developing a learning model which aims to produce a valid instructional model for teaching system of linear equations and inequalities. The results of the development is the combination of Two Stay Two Stray (TSTS) teaching strategy with outdoor learning method. The subject of the development of this model is the tenth grade science students of SMA N 1 Mojolaban. To test the effectiveness of this teaching strategy, the researcher conducted an experiment study with a 3x3 factorial design. The populations of this study was all students of tenth grade students of SMA in Sukoharjo district. The sample in this study was 338 students carried out by stratified cluster random sampling. The results of the study concluded that: (1) The results of the development in the form of combination between TSTS teaching strategy with learning methods or with several activities and games (2) TSTS teaching strategy combined with outdoor learning provided better achievement than the direct instructional method, yet it provided the same performance with TSTS teaching strategy. (3) Students with high emotional intelligence provide better learning achievement than students with moderate and low emotional intelligence, while the students with moderate emotional intelligence provided similar achievement with those who had low emotional intelligence (4) At each level of students’ emotional intelligence, TSTS teaching strategy combined with Outdoor learning provided better learning achievement than TSTS teaching strategy and direct instructional method, while TSTS teaching strategy provided better learning achievement than direct instructional model (5) At each learning model, students with high emotional intelligence provided better learning achievement than students with medium and low emotional intelligence, while students with medium emotional intelligence provided better learning achievement than students with low emotional intelligence.Keywords: Development, TSTS, Outdoor Learning